2009
DOI: 10.1089/vim.2008.0066
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of West Nile Virus in Ghana

Abstract: The epidemiology of West Nile virus (WNV) in Ghana, sub-Saharan Africa, and its relevance to transfusion were newly assessed. A total of 1324 plasma samples from five Ghanaian populations, including 529 children (<6 y old, pre-transfusion) and 795 adults (236 blood donors, 226 HIV-infected or non-infected pregnant women, 203 HIV symptomatic patients, and 130 AIDS patients) were screened for WNV RNA. No WNV RNA was detected, but 4.8% (13/271) and 27.9% (127/455) carried specific IgG in children and adults, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…During interepidemic periods in Egypt in 1991 [13], Uganda in 1984 [14], and the Central African Republic (CAR) in 1975 [15] and 1979 [16], the WNV-specific IgG prevalence rates were respectively 20%, 16%, 3% and 55%. In countries with no reported clinical cases or WNV isolation, WNV-specific IgG prevalence rates ranged from 0.9% in Kenya in 1987 [17] to 6.6% in Cameroon in 2000 [6] and 27.9% in Ghana in 2008 [18]. The high WNV-specific IgG prevalence detected in this survey suggests that this virus circulates actively in Gabon, despite the lack of reported clinical cases and the low prevalence (about 3%, 2/64) [10] detected in horses sampled in three Gabonese cities.…”
Section: Resultsmentioning
confidence: 99%
“…During interepidemic periods in Egypt in 1991 [13], Uganda in 1984 [14], and the Central African Republic (CAR) in 1975 [15] and 1979 [16], the WNV-specific IgG prevalence rates were respectively 20%, 16%, 3% and 55%. In countries with no reported clinical cases or WNV isolation, WNV-specific IgG prevalence rates ranged from 0.9% in Kenya in 1987 [17] to 6.6% in Cameroon in 2000 [6] and 27.9% in Ghana in 2008 [18]. The high WNV-specific IgG prevalence detected in this survey suggests that this virus circulates actively in Gabon, despite the lack of reported clinical cases and the low prevalence (about 3%, 2/64) [10] detected in horses sampled in three Gabonese cities.…”
Section: Resultsmentioning
confidence: 99%
“…[30][31][32] However, WN virus epidemiology in Africa differs from that seen in the United States or Romania where about one-fifth (20%) of WN virus human infections are symptomatic, and 1 in 150 (0.7%) develops neurological disease. 29,[33][34][35] These rates are much higher than those reported in Egypt and South Africa, where neurological disease is rare. 30,35 In addition, in countries like Senegal, seroprevalence of WN virus antibodies can be up to 80% in humans, horses, birds, and virus repeatedly isolated from mosquitoes and wild vertebrates hosts, however no WN virus outbreak has ever been reported.…”
Section: Introductionmentioning
confidence: 99%
“…29,[33][34][35] These rates are much higher than those reported in Egypt and South Africa, where neurological disease is rare. 30,35 In addition, in countries like Senegal, seroprevalence of WN virus antibodies can be up to 80% in humans, horses, birds, and virus repeatedly isolated from mosquitoes and wild vertebrates hosts, however no WN virus outbreak has ever been reported. 6,36 -40 These observations can be explained by the lack of appropriate WN surveillance, low pathogenicity of circulating isolates, low competence of local vectors, or exposure (and subsequent development of immunity) of a large proportion of the human To address those questions, we analyzed in this work, the vector competence of the Culex neavei group (in reference to morphological variation within Cx.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging or known but untested infectious agents were explored to determine the prevalence and potential feasibility and efficacy of screening. This was the case for GB virus‐C, West Nile virus, parvovirus B19, and human herpesvirus 8 24‐27. Syphilis was not tested for until a study was conducted and showed one case of likely transmission .…”
Section: Resultsmentioning
confidence: 99%